PABRIK KLOROFORM DARI NATRIUM HIDROKSIDA, KLORIN, DAN ASETON KAPASITAS 25.000 TON/TAHUN - , LILIK ADIB KURNIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Production facility of chloroform is designed with a capacity of 25.000 tons/year and operated continuously for 330 days/year and 24 hours/day. The product obtained is chloroform with purity 99,60%. The raw materials used are sodium hydroxide 48% as much as 14.838,18 kg/hr, acetone as much as1.549,26 kg/hr and chlorine as much as 6.386,20 kg/hr. Processes used inthe manufacture ofchloroformis ketones reduction,in this case is acetone. The process starts with the synthesis of sodium hypochlorite from sodium hydroxide and chlorine. Sodium hypochlorite solution reacts with acetone in a continuous stirred tank reactor. This reaction occurs in the liquid phase and takes place at a temperature of 60-75oC and 2 atm pressure. The heat of reaction is absorbed by the cooling water flowing in cooling coil and cooling jacket. The plant will be built at Cilegon, Province of Banten with a land area of 30 ha and will employ 188 personels. The plant needs 46.144,09 ton/year of steams, 77.995,85ton/year of water, 170.457,41 ton/year of natural gas, and 23.760.000 kWh/year of electricity. Fixed capital investment required is US$ 19.790.347,47 + Rp 186.934.848.123,18